Geologi Daerah Dulamayo Selatan, Kecamatan Telaga, Kabupaten Gorontalo - Mahmud, Vani Akbarani Y.; Permana, Aang Panji; Zainuri, Ahmad (Universitas Negeri Gorontalo, 2025)
The purpose of this research is to examine and interpret the geological setting of the Dulamayo Selatan area in Telaga District, Gorontalo Regency. The research addresses aspects of geomorphology, stratigraphy, and structural geology to develop a thorough understanding of the geological framework of the region. The methodology includes field surveys such as surface geological mapping, outcrop observations, and laboratory analysis for petrology and petrography. The findings indicate that the study area can be classified into two distinct geomorphological units: Lava Flow Ridge and Intrusive Hills. The stratigraphy comprises two rock units: the andesite unit, consisting of andesite and altered andesite, and the granodiorite unit. Structurally, the area is dominated by tension joints with a primary northeast-southwest orientation. It is expected that the findings of this study will contribute to a better understanding of the geological conditions of the region and assist in efforts related to natural resource utilization and the mitigation of geological risks in Dulamayo Selatan.